Growing your business globally - Taft, Robert A. ([Mason, Ohio] : Thomson, 2005)
[This book] tries to set a new international business environment and takes the reader step-by-step from company assessment of export readiness through the strategic export process. [It] tackles international business operations, and looks at the best practices of companies in these operations. [It also] culminates with a negotiation between two companies from different countries to develop a single international joint venture. -Dust jacket
Includes bibliographical references and index
Keywords: International business enterprises